2021
DOI: 10.3389/fpsyg.2021.612224
|View full text |Cite|
|
Sign up to set email alerts
|

Acceptance of Diversity as a Building Block of Social Cohesion: Individual and Structural Determinants

Abstract: High levels of social cohesion have been shown to be beneficial both for social entities and for their residents. It is therefore not surprising that scholars from several disciplines investigate which factors contribute to or hamper social cohesion at various societal levels. In recent years, the question of how individuals deal with the increasing diversity of their neighborhoods and society as a whole has become of particular interest when examining cohesion. The present study takes this a step further by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 73 publications
0
1
0
Order By: Relevance
“…Moreover, its concept and methodology have also been applied to Germany at the federal state level (Dragolov et al 2016, Ch. 7), regional level (Arant et al 2017;Dragolov et al 2019;Follmer et al 2020;Boehnke et al 2022), and neighborhood level (Arant et al 2016). To the best of our knowledge, this application of one and the same concept at various socio-spatial levels ranging from major world regions to city areas is unmatched in cohesion research.…”
Section: K 5 Discussion and Conclusionmentioning
confidence: 99%
“…Moreover, its concept and methodology have also been applied to Germany at the federal state level (Dragolov et al 2016, Ch. 7), regional level (Arant et al 2017;Dragolov et al 2019;Follmer et al 2020;Boehnke et al 2022), and neighborhood level (Arant et al 2016). To the best of our knowledge, this application of one and the same concept at various socio-spatial levels ranging from major world regions to city areas is unmatched in cohesion research.…”
Section: K 5 Discussion and Conclusionmentioning
confidence: 99%
“…This definition of social cohesion has been adopted in the Social Cohesion Radar of Bertelsmann Stiftung (see Figure 1), which the present study draws on. It has been applied to comparisons of cohesion across countries (see Dragolov et al, 2016, for a comparison of 34 Western societies, Dragolov et al, 2018, for a comparison of 22 Asian societies), regions of Germany (see Arant et al, 2017, for a comparison of 79 regions), and neighborhoods (see Arant et al, 2016, for a comparison of neighborhoods of Bremen). The Baden-Württemberg studies reported here belong to the series looking at subnational units within Germany.…”
Section: Social Cohesion As Resilience Factormentioning
confidence: 99%
“…A concerted effort to wrestle with these affairs be made if Kambians are to imagine a socially cohesiveness society in which folk's every day experiences are acknowledged and not taken for granted. As Arant et al (2021) argues that social cohesion is about getting by and getting on with the mundanities of everyday life and that "Cohesive societies is related to prevailing mentalities of individuals once the social structure of a community is accounted for". It is at these mundane thresholds and mentalities that Kambians need to zoom in and pay attention to the perpetual constraints with which many Susu-Guineans continue to contend.…”
Section: Constraints and Potentialsmentioning
confidence: 99%